2016
DOI: 10.3389/fphys.2016.00035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Coordination after Training and Detraining. A Principal Component Analysis Approach

Abstract: Our purpose was to study the effects of different training modalities and detraining on cardiorespiratory coordination (CRC). Thirty-two young males were randomly assigned to four training groups: aerobic (AT), resistance (RT), aerobic plus resistance (AT + RT), and control (C). They were assessed before training, after training (6 weeks) and after detraining (3 weeks) by means of a graded maximal test. A principal component (PC) analysis of selected cardiovascular and cardiorespiratory variables was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(90 citation statements)
references
References 27 publications
7
82
1
Order By: Relevance
“…Similar studies of CRC during exercise (Balagué et al, 2016) have reported medium and large effect sizes. Thus, using an effect size of d = 0.7, α < 0.05, power (1—β) = 0.80, we estimated a sample size = 15.…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Similar studies of CRC during exercise (Balagué et al, 2016) have reported medium and large effect sizes. Thus, using an effect size of d = 0.7, α < 0.05, power (1—β) = 0.80, we estimated a sample size = 15.…”
Section: Methodssupporting
confidence: 61%
“…Other commonly registered variables in cardiorespiratory testing, such as respiratory equivalents, respiratory exchange ratio, oxygen pulse, oxygen consumption, etc., were excluded from the analysis due to their known deterministic mathematical relation with the aforementioned variables (Balagué et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Our idea for future studies is to design experimental work that can identify in advance responders and non-responders with the aim of creating a pre-training schedule that can be modified to help non-responders improve their performance. In this sense, incorporating complex system approaches, such as those reported by Balagué et al (2016) and Garcia-Retortillo et al (2017) on cardiorespiratory coordination, will be of great value in assessing a strategic research framework for individual training prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…PCA has been used in the past three decades as an efficient method of defining the essential, i.e., collective, variables in a range of complex dynamical processes such as protein folding (Matsunaga et al, 2007 ; Hayward and De Groot, 2008 ; Maisuradze et al, 2009 ) and brain dynamics (Jirsa et al, 2002 ). In sport science, PCA has allowed identifying the performance of an interpersonal precision task (Ramenzoni et al, 2012 ) to determine the impact of different training programs on cardio-respiratory coordination (Balagué et al, 2016 ), and to identify different dancing coordination patterns depending on concrete task constraints (Bronner and Shippen, 2015 ; Torrents et al, 2015 ). In soccer, PCA has been applied to capture player positional patterns and their variability (Barros et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%